UPAYA LPMD DALAM MENINGKATKAN KESEJAHTERAAN EKONOMI MASYARAKAT DI DESA TRI MANDAYAN - Suherdi, Suherdi; Genjik, Bambang; Syahrudin, Husni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
ABSTRACTThis research aims to find out and explore what efforts have been made and will be done by thevillage community empowerment agency (LPMD) with the village government to improve the economic welfare of the community in the village of Tri Mandayan. This research uses qualitative case study approach method. The data source in this study is LPMD management, village government, and the community. Data collection techniques used are observation, documentation, and in-depth interviews. The results showed that development and empowerment efforts that have been made, had a good impact, in improving the economic welfare of the community. Efforts made already covered from various fields including education, health, road infrastructure, village facilities and infrastructure, community empowerment, social assistance for the poor and others. But the shortcomings that are owned by every member of LPMD with a lack of understanding and carrying out tasks and their function as an institution in the midst of society. That is also due to lack of training and initial training provided by the village government to LPMD members coupled with lack of participation and member awareness will be the mandate that is being carried. This affects the slowness the development process to be carried out.Keywords : Community Economic Welfare, Empowerment and Development Efforts, Village Community Empowerment Institute.